2005
DOI: 10.1002/ange.200462057
|View full text |Cite
|
Sign up to set email alerts
|

Mass Production and High Photocatalytic Activity of ZnS Nanoporous Nanoparticles

Abstract: Die Selbstorganisation hexagonaler 3 bis 5 nm großer ZnS‐Nanokristalle kann zur Herstellung großer Mengen an nanoporösen Zinksulfid‐Nanopartikeln (ZnS‐NPNPs) genutzt werden. Die einheitlichen, sphärischen NPNPs sind monodispers und haben spezifische Oberflächen von 156 m2 g−1. Sie katalysieren bei Raumtemperatur den Photoabbau von Eosin B wirkungsvoller als das Titandioxid Degussa P25 oder ZnS‐Nanokristalle (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(112 citation statements)
references
References 41 publications
3
108
0
Order By: Relevance
“…It is noteworthy that the highest quantum yields of CO 2 photoreduction, in the range of 10-80%, were obtained, by various research groups [144,145,148,149,155,273], with ZnS nanoparticlesanalogues to those ejected by hydrothermal vents. These nanoparticles are particularly photosynthetically active since the probability of electron trapping at the surface increases with the surface/volume ratio [241,276]. Studies of the photoelectrochemical reduction of CO 2 at p-type semiconductors showed that at high CO 2 pressure the rate of reduction was principally limited only by light intensity [277].…”
Section: Photosynthesis In the Zn Worldmentioning
confidence: 99%
“…It is noteworthy that the highest quantum yields of CO 2 photoreduction, in the range of 10-80%, were obtained, by various research groups [144,145,148,149,155,273], with ZnS nanoparticlesanalogues to those ejected by hydrothermal vents. These nanoparticles are particularly photosynthetically active since the probability of electron trapping at the surface increases with the surface/volume ratio [241,276]. Studies of the photoelectrochemical reduction of CO 2 at p-type semiconductors showed that at high CO 2 pressure the rate of reduction was principally limited only by light intensity [277].…”
Section: Photosynthesis In the Zn Worldmentioning
confidence: 99%
“…22 In photocatalysis, particularly when using CN photocatalysts, morphology and surface area, in relation to the effective charge separation, are important parameters. [23][24][25][26][27][28][29][30] Density functional theory (DFT) is a useful and powerful technique to obtain the relevant photophysical and optoelectronic parameters of a given photocatalyst. 31,32 In addition to structure determination, DFT calculations can lead to the simulation of several semiconductor properties such as the bandgap, the dielectric constants and band positions, with good accuracy thanks to recently developed functionals such as HSE06.…”
Section: Introductionmentioning
confidence: 99%
“…Typical examples are in flat-panel displays, electroluminescence devices, IR windows [11,12], sensors, lasers, and ultraviolet-emitting diodes [13,14]. Due to its non-toxicity, zinc sulphide is now used in waste water treatment as a photocatalyst in the degradation of organic pollutants such as dyes, halogenated derivatives, and pnitrophenol [15][16][17][18]. ZnS can be prepared in various dimensions, such as isotropic dots, spheres, and anisotropic sheets, platelets, and diskettes [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%